Construction of a highly sensitive signal electrochemical sensor based on self-assembled cobalt oxide-hydroxylated single-walled carbon nanotubes composite for detection of dopamine in bovine serum samples. Issue 5 (October 2021) - Zou, Jiao; Guan, Jin-Feng; Zhao, Guo-Qing; Jiang, Xin-Yu; Liu, Yi-Ping; Yu, Jin-Gang; Li, Wen-Jie
Abstract: A novel electrochemical sensor based cobalt oxide nanoparticles and hydroxylated single-walled carbon nanotubes composite (Co3 O4 /SWCNTs-OH) for the highly sensitive detection of dopamine (DA) was successfully developed in present work. Spinel Co3 O4 crystals were synthesized by a facile hydrothermal process without high-temperature calcination procedure, and then self-assembled with SWCNTs-OH. The obtained Co3 O4 /SWCNTs-OH composite possesses large surface area and cross-linked structure. The morphology, compositions, surface functional groups, and crystal structure of Co3 O4 /SWCNTs-OH composite were characterized by Field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). The electrochemical properties and catalytic performance of prepared sensor (Co3 O4 /SWCNTs-OH/GCE) were studied by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammetry (DPV). These results showed that Co3 O4 /SWCNTs-OH/GCE exhibited excellent electrocatalytic performance in terms of DA oxidation peak potential and current density in comparison with bare GCE, Co3 O4 /GCE and SWCNTs-OH/GCE. Under optimum conditions, Co3 O4 /SWCNTs-OH/GCE exhibited a good linear relationship between DA concentrations and current responses in the range 1–100 μM. Low detection limit of 0.08 μM (signal-to-noise ratio of 3, S/N = 3) and high sensitivity of 1.427 μA μM −1 could be observed at Co3 O4 /SWCNTs-OH/GCE. In addition, the quantitative detection of DA in bovine serum samples at Co3 O4 /SWCNTs-OH/GCE showed satisfactory recoveries (93.68–105.47%) and low relative standard deviation ( RSD ) (3.02–5.83%). The outstanding sensitivity, good selectivity and reproducibility of Co3 O4 /SWCNTs-OH/GCE might be attributed to the synergistic effects between Co3 O4 and SWCNTs-OH. The fabricated Co3 O4 /SWCNTs-OH composite might be used as a promising catalyst for the practical electrochemical detection of DA. Graphical Abstract: ga1 Highlights: The synergistic effect of Co3 O4 and SWCNTs-OH is performed to the electrocatalysis of DA. Co3 O4 /SWCNTs-OH/GCE shows high sensitivity toward DA. Co3 O4 /SWCNTs-OH/GCE could be used for determination of DA in physiological fluids.